Microwave-assisted synthesis of mn2po4f and application in rechargeable aqueous sodium-ion batteries - Nzimande, Nkosikhona Thabani Mphephethwa (My University, 2020)
Sodium-ion batteries (SiBs) are set to be an alternative energy storage system to help ease the lithium-ion batteries (LiBs) market demands and availability. On the other hand, zinc-metal based anode aqueous batteries are paving the way in cost-effective, environmentally friendly, and non-toxic batteries. Here, we attempt to develop a zinc-metal based anode that uses sodium-ion as an electrolyte to form an aqueous battery that is mildly acidic. The material under investigation is the triplite (Mn2PO4F) also known as DiManganese fluorophosphate (MPF), it is a pinkish mineral that has no known reported electrochemical properties such as behaviour and performance. This is the main reason why it sparked our interest. It is known that manganese-based battery materials suffer from these major obstacles: (i) Mn dissolution and (ii) Jahn teller distortions that lead to capacity fading and poor electrochemical performance. Knowing this, our purpose was to synthesize the triplite (Mn2PO4F) using microwave synthesis and use 2%-CeO2 as a coating to help stabilizes the materials integrity and improve its electrochemical performance, also coat the material using 15% carbon (from citric acid) as an in-situ and ex-situ (from carbon black) coating agents to aid in improving the materials conductivity and electrochemical performance. This gave rise to four materials to be studied, MPF, MPF-CeO2, MPF-CeO2-CB and MPF-CeO2-C (CB – carbon black, C – citric acid) and put into test using a T-type-cell as a battery. To generate more detailed results, we decided to separate the results, with MPF and MPF-CeO2 forming chapter four of the results sections and MPF-CeO2-CB and MPF-CeO2-C forming chapter five of the results section. In chapter four the results obtained for MPF at 0.1C had 2.2 mAhg-1 maintaining 60% of its initial capacity with ± 99% CE and MPF-CeO2 at 0.1C had 101.61 mAhg-1 maintaining 90% of its initial capacity lasting only 400 cycles cycled at 5C with ± 99% CE. The analysis of the kinetic responses reveal that MPF at 1.0 C is seen to represent transitions between battery-type and pseudocapacitive reactions or process which are mainly kinetically dominated by diffusion-controlled process making it a good candidate for battery materials and MPF-CeO2 electrochemical reactions are simultaneously controlled by semi-infinite linear ionic diffusion and partially by surface-controlled capacitive behavior making it a much better battery material than MPF. Overall MPF-CeO2 is the best material to be used in aqueous SiBs mainly due to the CeO2 coating. Chapter five results obtained for MPF-CeO2-CB at 0.1C. had 22.60 mAhg-1 maintaining 64.24% of its initial capacity after 1000 cycles cycled at 1C with ± 99% CE and MPF-CeO2-C at 0.1C had 195.16 mAhg-1 maintaining 19.91% of its initial capacity after 100 cycles with ± 99% CE. The kinetic responses reveal that MPF-CeO2-CB kinetically dominated by the diffusion-controlled process and MPF-CeO2-C is simultaneously controlled by both ionic-diffusion and capacitive-control, this makes MPF-CeO2-C the most desirable battery material for zinc-metal anode aqueous sodium-ion batteries, however, MPF-CeO2-CB ex-situ coating is more stable than MPF-CeO2-C over 100 cycles. Overall MPF-CeO2 from chapter four and MPF-CeO2—C from chapter 5 are the best suited materials to be used for rechargeable aqueous sodium-ion batteries.
A dissertation submitted for a degree of Masters of Science to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2020